Rewiring from Within: Exploring how Participation in Curriculum Development Impacts Engineering Academics Professional and Personal Well-being - Smith, Lelanie; Hechter, Janine; Ebersöhn, Liesel; Swartz, Bronwyn; Direito, Inês (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Addressing complex global challenges requires more than technical solutions; it demands an integrated approach involving economic, environmental, and social dimensions. Engineering education is a driver for Sustainable Development Goals (SDGs), but transformative engineering education requires a ‘shift of consciousness’ and focus on socio-emotional development. Our project developed a process called ’Clear,’ rooted in Theory U for systemic transformation in engineering education and applying meta-patterns to support shifts in personal perspectives. The process enables engineering educators to slow down and explore fundamental questions about identity, purpose, and response-ability, which are essential precursors to effective engagement with complexities of developing an engineering curriculum. This approach is particularly relevant for developing innovative engineering curricula in South Africa and in comparable low- and middle income settings transforming away from inequality to justice. The study aims to explore how focusing on intrapersonal transformation, through the ’Clear’ process, can facilitate systemic change in engineering higher education. Specifically, it explores personal awareness and development as foundational intrapersonal capacities to enable broader curriculum shifts. Research assistants conducted online interviews with 34 engineering educators engaged in the ’Clear’ process. Audio-recorded interviews were transcribed verbatim and analysed using inductive thematic analysis to understand the participants’ experience during and after the ‘Clear’ process. The analysis revealed themes such as the importance of community, the need for balanced reflective practice, and the interplay between intrinsic and extrinsic motivations for change. Participants highlighted the role of networking and the complexities of building learning communities, with their narratives showing evidence of both professional and personal well-being as a result of participating in the curriculum intervention. These insights suggest that individual transformation is crucial before addressing larger institutional goals, aligning with the principles of the Inner Development Goals (IDGs) framework. This work-in-progress suggests that integrating IDGs, such as “Being” into academic development can create a foundation for innovative, student-centred curricula. Future research will explore how individual attributes - such as career phase, personality, and socio-cultural values - shape engagement with systemic transformation efforts.